2003
DOI: 10.1097/01.wnr.0000073684.00308.c0
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of action in schizophrenia

Abstract: An abnormal sense of agency is among the most characteristic yet perplexing positive symptoms of schizophrenia. Schizophrenics may either attribute the consequences of their own actions to the intentions of others (delusions of influence), or may perceive themselves as causing events which they do not in fact control (megalomania). Previous reports have often described inaccurate agency judgements in schizophrenia, but have not identified the disordered neural mechanisms or psychological processes underlying t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
69
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(79 citation statements)
references
References 20 publications
(38 reference statements)
8
69
1
1
Order By: Relevance
“…tendency to attribute what they see to their own agency, despite visual discrepancies (Daprati, et al, 1997, Fourneret, et al, 2001, Haggard et al, 2003, Synofzik et al, 2008. In this regard, we could not detect any difference in attribution style between schizophrenia patients with-and without first-rank symptoms.…”
Section: Sense Of Agency Deficits In Schizophreniacontrasting
confidence: 65%
See 1 more Smart Citation
“…tendency to attribute what they see to their own agency, despite visual discrepancies (Daprati, et al, 1997, Fourneret, et al, 2001, Haggard et al, 2003, Synofzik et al, 2008. In this regard, we could not detect any difference in attribution style between schizophrenia patients with-and without first-rank symptoms.…”
Section: Sense Of Agency Deficits In Schizophreniacontrasting
confidence: 65%
“…This is also reflected in the schizophrenia literature with respect to speech attribution (Johns et al, 2001, Johns et al, 2006, Stephane et al, 2009) and also with respect to incorrect agency attribution either to external sources or to the self (Daprati, et al, 1997, Fourneret, et al, 2001). In the majority of agency manipulation studies schizophrenia patients showed a tendency similar to that in our study, namely, atendency to attribute what they see to their own agency, despite visual discrepancies (Daprati, et al, 1997, Fourneret, et al, 2001, Haggard et al, 2003, Synofzik et al, 2008. In this regard, we could not detect any difference in attribution style between schizophrenia patients with-and without first-rank symptoms.…”
supporting
confidence: 73%
“…For example, diminished SoA associated with increased TRE (Timm, Schönwiesner, SanMiguel, & Schröger, 2014) would result in attributing self-generated thoughts and actions to an external force in schizophrenia. Patients with schizophrenia showed a similar increased contraction of subjective time between their voluntary action and its consequence through an intentional binding paradigm (Haggard, Martin, Taylor-Clarke, Jeannerod, & Franck, 2003;Maeda et al, 2012;Voss et al, 2010). Given that visual sensory adaptation could be transferred to auditory TRE (Heron et al, 2009;Sugano et al, 2010Sugano et al, , 2012, this transference effect would need to be examined in patient studies when examining auditory TRE for future interventional studies.…”
Section: Figure 4 About Herementioning
confidence: 99%
“…. Baseline judgements vary widely both across people and across groups (Haggard, Martin, Taylor-Clarke, Jeannerod, & Franck, 2003), and may reflect individual strategies in the attention paid to the clock. In order to control for such individual differences, each participant's judgement in the baseline condition is subtracted from their judgement in the agency conditions.…”
Section: Cross-modal Synchronisationmentioning
confidence: 99%